2001
DOI: 10.1108/01437730110389247
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between empowerment, job satisfaction and reported stress levels: some Australian evidence

Abstract: The role of empowerment of subordinates has been an ongoing argument since the 1950s and 1960s following the work of social scientists like Likert and Herzberg. It is argued that empowerment can improve the productivity of the organization. The catch cry of the 1900s and 2000s has been that organizations must be more productive: this could be partly achieved by reducing the workforce and empowering the survivors to make decisions affecting them. The data for this study were collected by the federal government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 20 publications
6
53
0
3
Order By: Relevance
“…Also employees' perceptions of empowerment was positively related to Empowerment methods and techniques for sport managers 122 organizational commitment (except the dimension of competence). (Savery & Luks, 2001).…”
Section: Empowerment Methods and Techniques For Sport Managersmentioning
confidence: 99%
“…Also employees' perceptions of empowerment was positively related to Empowerment methods and techniques for sport managers 122 organizational commitment (except the dimension of competence). (Savery & Luks, 2001).…”
Section: Empowerment Methods and Techniques For Sport Managersmentioning
confidence: 99%
“…Research has shown that organisational change, such as downsizing, implementation of new equipment or plant and restructuring, can and often does lead to stress and increases in injury/illness (Rees & Redfern, 2000;Savery & Luks, 2001;Morris et al, 2006). In a study conducted by Sharpley and coworkers (1996) on university staff in Monash University, Australia, the most commonly reported sources of job stress were (in order of frequency): "lack of regular feedback about how well I am doing my job"; "lack of promotion opportunities"; "uncertainty about how amalgamations will influence me"; "overwork"; "being expected to do too much in too little time"; "lack of necessary equipment and/or infrastructure support".…”
Section: Possible Causes Of Stress In Higher Educationmentioning
confidence: 99%
“…Role ambiguity refers to the uncertainty, on the part of employees, about key requirements of their jobs, and about how they are expected to behave in those jobs (Nhundu, 1999;Conley & Woosley, 2000;Koustelios et al, 2004). Role conflict occurs when different groups or persons with whom an individual must interact hold conflicting expectations about that individual's behaviour and can result from inconsistent information (Koustelios et al, 2004;Johnson et al, 2005;Nwadiani, 2006;Chang & Lu, 2007).Research has shown that organizational change, such as downsizing, implementation of new equipment or plant and restructuring, can and often does lead to stress and increases in injury/illness (Savery & Luks, 2001;Morris et al, 2006). In a study conducted by Sharpley and co-workers (1997) on university staff, the most commonly reported sources of job stress were (in order of frequency): "lack of regular feedback about how well I am doing my job"; "lack of promotion opportunities"; "uncertainty about how amalgamations will influence me"; "overwork"; "being expected to do too much in too little time"; "lack of necessary equipment and/or infrastructure support".…”
mentioning
confidence: 99%
“…임파워먼트는 개인이 자신의 직무역할과 직무환경을 능 동적으로 통제할 수 있는 것을 의미하며 (15) , 따라서 임파 워먼트가 근무자에게 힘(power)과 통제(control)와 권위 (authority)를 부여하는 일련의 직무활동이라는 점에서 직 무스트레스와 큰 관련성이 있다고 알려져 있다 (16) . 또한 요 구-통제 스트레스 모델(demand-control stress model)에 따 르면 직장에서의 통제감은 개인의 안녕에 영향을 미치는 직무스트레스를 완화하는 것으로 나타났다 (17) . 국내에서는 119 구급대원을 대상으로 한 연구에서 임파워먼트와 직무 만족은 강한 상관관계가 있으며 임파워먼트는 직무만족에 영향을 미침을 나타냈으며 (18) , 간호사들을 대상으로 한 연 구에서는 특히 응급한 상황에서 임파워먼트 지각수준이 높을수록 직무스트레스는 낮아지는 것이 보고되었다 (19) .…”
Section: 서 론unclassified